KOMPONEN MATERI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN ORIENTASINYA PADA MADRASAH IBTIDAIYAH - Uci Nurhayati; Muhammad Nu’man (Universitas Islam Lamongan, 2022)
PAI material is the subject matter or subject matter in the field of Islamic studies which is carried out in a planned manner in order to prepare students to recognize, understand, appreciate, believe in, practice Islamic teachings and have Islamic character and be followed by guidance to respect other religions concerning harmony between religious communities until realized national unity and integrity. Islamic religious education is given by following the guidance that religion is taught to humans with a vision to create humans who fear Allah SWT and have noble character and aim to produce honest, fair, virtuous, ethical, mutual respect, disciplined, harmonious, and productive humans. Both personal and social. In this case, it is applied through education. Education is the first and most important guide for a Muslim. Thus, it is necessary to instill in students to become individuals who understand and understand religious teachings and practice them in everyday life. The research method used is a type of library research.